2020
DOI: 10.1177/1074248420953271
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone and Training-Induced Cardiac Remodeling Improve Cardiac Function and Arterial Pressure in Spontaneously Hypertensive Rats

Abstract: Introduction: Dexamethasone (DEX)-induced hypertension and cardiac remodeling are still unclear, especially in spontaneously hypertensive rats (SHR). On the other side, exercise training is a good strategy to control hypertension. Therefore, this study investigated the effects of DEX treatment and physical training on arterial pressure and cardiac remodeling in SHR. Material and Methods: SHR underwent treadmill training (5 days/week, 1h/session, at 50-60% of maximal capacity, 0% degree, 75 days) and received l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 57 publications
8
19
1
Order By: Relevance
“…The results of the present study showed that low‐dose (50 μg/kg) of DEX treatment changed the autonomic control to the heart in Wistar rats, which in part contributed to increase BP, but the higher sympathetic drive to the heart, already present in SHR, was maintained after the DEX treatment period. These results agree with our recent publication (Duchatsch et al, 2020), which was the first study investigating the effects of this dose of DEX and exercise training in SHR.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The results of the present study showed that low‐dose (50 μg/kg) of DEX treatment changed the autonomic control to the heart in Wistar rats, which in part contributed to increase BP, but the higher sympathetic drive to the heart, already present in SHR, was maintained after the DEX treatment period. These results agree with our recent publication (Duchatsch et al, 2020), which was the first study investigating the effects of this dose of DEX and exercise training in SHR.…”
Section: Discussionsupporting
confidence: 93%
“…The first part of this present study showed that SHR presented higher BP accompanied by autonomic unbalance to the heart, represented by higher LF and lower HF compared with Wistar rats, therefore confirming that hypertension, already installed in SHR, is generally accompanied by inappropriate neural adjustments (Bertagnolli et al, 2006; Duchatsch et al, 2020; Masson et al, 2015; Stern et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations